Monitoring Agitated Behavior After acquired Brain Injury: Onset, Duration, Intensity, and Nursing Shift Variation. Issue 5 (6th November 2015) - Aadal, Lena; Mortensen, Jesper; Nielsen, Jørgen Feldbæk
Abstract: Purpose: To describe the onset, duration, intensity, and nursing shift variation of agitated behavior in patients with acquired brain injury (ABI) at a rehabilitation hospital. Design: Prospective descriptive study. Methods: A total of 11 patients with agitated behavior were included. Agitated behavior was registered with the Agitated Behavior Scale (ABS). The nurse or therapist allocated the individual patient assessed ABS during each shift. Intensity of agitated behavior was tested using exact test. A within‐subject shift effect was analyzed with repeated‐measure ANOVA. Findings: The onset of agitated behavior was at a median of 14 (1–28) days from admission. Seven patients remained agitated beyond 3 weeks from onset. Severe intensity of agitation was observed in 86 of 453 nursing shifts. Differences in agitated behavior between day, evening, and night shifts were found, F(2.20) = 7.90, p = .008, with tendencies of increased agitated behavior in day and evening shifts compared to night shifts. Conclusion: Agitated behavior had a late onset, was severe, and long‐lasting in the present sample of patients. Clinical Relevance: The study increases awareness on the potential challenge of agitated behavior in patients with ABI.